Investigating the influence of divertor baffles on nitrogen-seeded detachment in TCV with SOLPS-ITER simulations and TCV experiments - G. Sun; H. Reimerdes; C. Theiler; B.P. Duval; M. Carpita; C. Colandrea; R. Ducker; O. Février; S. Gorno; L. Simons; E. Tonello; the EUROfusion Tokamak Exploitation Team; et al. (Nuclear Fusion)
Plasma edge simulations with the SOLPS-ITER code are performed to study the influence of divertor baffles on nitrogen-seeded detachment in Tokamak à Configuration Variable (TCV) single-null, L-mode discharges. Scans of nitrogen seeding rate are conducted in both baffled and unbaffled TCV divertors, where the nitrogen seeding with baffles is found to yield lower target temperatures and heat fluxes than with baffles-only and with seeding-only. The cumulative effects of baffles and seeding on target parameters are interpreted by the two-point model. The divertor neutral density and neutral compression increase with baffles, due to lower divertor to main chamber neutral conductance, as explained by a schematic neutral transport model with baffles. The nitrogen retention, defined as the ratio of average nitrogen nuclei density in divertor and main chamber, increases with the seeding rate if baffled, and remains constant if unbaffled. At the same outboard mid-plane separatrix plasma density, the nitrogen retention with baffles is lower than the unbaffled retention at low seeding levels and is higher at high seeding levels, which is explained by the changes of nitrogen ion and neutral transport with baffles and seeding. The baffled carbon retention is higher than the unbaffled retention due to lower divertor to main chamber carbon neutral conductance. Baffles increase the divertor radiation. The predicted trends of target parameters, the distribution of neutrals and radiations are well supported by TCV experiments, though discrepancies in the absolute values remain. The simulations yield an overall colder and denser divertor, consistent with previous SOLPS-ITER simulations of Ohmically heated L-modes in TCV. The successful comparison of simulation and experiment, together with the understanding gained from the neutral transport model, increases the confidence in the SOLPS simulations for the next TCV divertor upgrade.